Juvenile Criminal Behavior and Peers’ Influences: A Comparative Study in the Brazilian Context - Rezende Bazon, Marina; Departament of Psychology São Paulo University (2012)
This study investigates aspects of living with peers in adolescent offenders in the Brazilian context based on the social and personal control behavior theory developed by Marc Le Blanc and his colleagues. Both comparative and quantitative approaches were used to study two groups: Delinquents/adjudicated and control. A questionnaire developed by Le Blanc and adapted to the reality of the study was applied to 75 participants. A significant level of 0.05 was adopted and the data analysis showed that delinquents developed poor relationships suggesting an experience of greater socio-emotional isolation. This refers to the problematic experience in one of the major developmental tasks of this period. Further studies should be developed to analyze the interactions between the coexisting aspects in the family, at school and with peers.